Profile of Cytostatic Drug Use in Breast Cancer Patients (Mammae carcinoma) at Medan Hospital - Sitepu, Nadroh; Pasaribu, Romaito; Hastuty, Yulina Dwi (Poltekkes Kemenkes Palu, 2023)
Breast cancer is the most common type of cancer in the world (2,261,419 cases) and in Indonesia (65,858 cases). This research aims to determine the class and type of cytostatic drugs most frequently used in breast cancer chemotherapy patients from January to March 2023 at RSUP Haji Adam Malik Medan. This study used a descriptive survey method with a saturated sample of 176 medical records. Data collection was done retrospectively by gathering information from the electronic medical records of the patients. The research results show that the characteristics of the patients are as follows: the majority were female, totalling 176 patients (100%). The most common age group was 45-54 years, with 111 patients (63.1%), and the prescription of cytostatic drugs was highest in March, with 80 patients (36.9%). In conclusion, the most commonly used class of cytostatic drugs was antibiotics, with 146 cases (32.88%), and the most commonly used type of cytostatic drug was Doxorubicin, with 114 cases (25.68%). This indicates that the use of antibiotics is a significant part of breast cancer treatment, and it is important to pay attention to the safety and regularity of drug use to prevent drug resistance and the severity of the disease.